Effects of public policies on the preferences and orientation of the activities carried out by academics in STEM areas of IES de México - González Bello, Edgar Oswaldo; Estévez Nenninger, Etty Haydeé; Del Cid García, Carlos Javier (Education Policy Analysis Archives, 2019)
This study analyzes the effects of some of Mexico's public policies on preferences and time dedicated to teaching and research activities, including research type and orientation as well as innovative activities and and dissemination of knowledge, according to academics from different types of higher education institutions. For this purpose, a questionnaire was used that was answered by 301 academics of science, technology, engineering and mathematics (STEM), assigned to the 34 State Public Universities (UPES) and 17 Public Research Centers (CPI) of CONACyT. With respect to the 2007 national survey, the results show changes in the preferences of academics: a decreased inclination toward teaching and an increase in the preference for the research activities of UPES scholars, despite high numbers of weekly hours devoted to teaching. In the CPI portion, the predominant tendency towards research, and mainly applied research, is maintained. For both types of institutions, little time is dedicated to the tasks of linkage and academic management.